Perancangan UMKM Keripik Kentang Mustofa Berbasis Teknologi di Lingkungan PKK RT.004 RW.008 Griya Alam Sentosa-Cileungsi-Bogor - Caswito, Ade; Sulastri, Sulastri; Yuwono, R. Sapto; Lisdiana, Lisdiana; Prabowo, Eri; Adi, Tri Wahyu; Ahsan, Muh; Prayudi, Prayudi; Ananda, Shafia; Tambun, Johan Rivaldo (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
Community Service (PKM) Summary: Empowering Technology-Based Small and Medium Enterprises (SMEs). This Community Service (PKM) aims to enhance the economic empowerment of Micro, Small, and Medium Enterprises (MSMEs) in the PKK RT.004 RW.008 Griya Alam Sentosa-Cileungsi-Bogor community. The project, titled designing Mustopa Potato Chips SMEs Based on Technology, is conducted by the Entrepreneurship/Business Energy Program at IT-PLN. Utilizing a descriptive statistical approach, we assess the training's effectiveness, including participant profiles, feedback, and outcomes. The results encompass increased entrepreneurial design knowledge and assistance in developing technology-based businesses for MSME players. This initiative supports MSME growth and strengthens the relationship between IT-PLN and the community.